The impact of government transfer payment frequency on consumption: Evidence from delayed UI - Michael Gelman; Zachary Orlando; Dhiren Patki (Federal Reserve Bank of Boston, 2024)
We study how the frequency of government transfer payments affects spending behavior. Our empirical approach uses transaction-level data on income and spending and exploits quasi-random delays in the receipt of unemployment insurance (UI) benefits. Spending drops by about half of the loss in income that occurs while individuals wait for UI benefits, revealing the value of periodic payments for liquidity-constrained individuals. Once delayed payments are received as lump sums, individuals reallocate spending toward less commonly purchased big-ticket categories that are dominated by durables. Our findings suggest that transfer programs with mixed frequencies, such as advance disbursements of lump-sum tax credits, can be beneficial to recipients.
Keywords: E21; H53; H31; 330; Consumption smoothing; unemployment benefits; liquidity shocks